Oil Benchmarks - Bassam Fattouh; Owain Johnson (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2018)
This issue of the Oxford Energy Forum is devoted to analysing the role of oil benchmarks, their evolution over time, the challenges facing the most established benchmarks, and the extent to which the current transformations in oil market fundamentals and crude trade flows as well as changes in the regulatory environment are likely to result in the emergence of new benchmarks and new crude oil pricing systems.
Keywords: 330